Surgical treatment of the pathology of the aortic valve and ascending aorta using minimally invasive access - Vayda, V. V.; Kravchenko, V. I.; Zhekov, I. I.; Kravchenko, I. M.; Lazoryshynetz, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Despite the obvious advantages of longitudinal median sternotomy as an operative access to the heart, modernity re-quires cardiac surgeons to perform complex interventions by minimizing surgical trauma with a decrease in time spent by patients in a hospital. Taking into account that the application of minimally invasive access in the correction of aortic valve diseases in combination with the ascending aorta pathology accelerates the functional recovery of patients, this issue requires a careful approach and the only correct choice of treatment. Purpose. Improvement of the results of surgical treatment of aortic valve and ascending aortic pathology by minimizing surgical trauma, rapid physical and psychosocial rehabilitation of patients. Materials and methods. Starting from 22.02.2014 to 01.04.2018, 86 patients were treated for the correction of aortic heart disease in combination with an ascending aorta aneurysm or without using the upper J-shaped ministernotomy for access. Conclusions. The method for correction of aortic valve defects in combination with an ascending aortic aneurysm through minimally invasive access allows to minimize surgical trauma, providing beautiful cosmetic effect and can be applied in clinical practice as an alternative to median sternotomy.